11.AMYLOID PRECURSOR PROTEIN IMMUNOHISTOCHEMICAL CHANGES IN THE NEWBORN MICE FRONTAL AND PARIETAL CEREBRAL CORTICES AFFECTED BY PRENATAL EXPOSURE TO KETAMINE (Iraqi Journal of Medical Sciences, 2018)
Background: Ketamine is N-methyl-D-aspartate (NMDA) receptors blocking drug, it affects the cerebral cortex and play an essential role in learning and memory. Amyloid ? (A?) is a cleavage product of a large, trans-membrane protein, termed amyloid precursor protein (APP); it may have a role in controlling synaptic activity.Objective: To investigate the immunohistochemical beta APP reaction in newborn mice frontal and parietal cerebral cortices after prenatal exposure to therapeutic doses of ketamine as an attempt for scientific judgments of making better understanding for effects of ketamine on developing brain, which may help to reduce adverse effects.Methods: Thirty pregnant mice were divided into two groups named experimental and control groups (15 mice for each groups). The experimental group animals were injected intraperitoneally with 50 mg/kg ketamine, the control group animals were injected with intraperitoneal distilled water. Paraffin sections of newborn mice frontal and parietal cortices were stained immunohistochmically with anti-APP antibodies.Results: The immunohistochemical labeling in the experimental group showed scattered clumps of brown staining distributed randomly in the cerebral cortex. The brown stained deposits vary also in shape and size, the larger and more intense staining was seen in the more superficial layers of the frontal cortex. The statistical analysis found non-significant differences in staining pattern between frontal and parietal cortices of control group, while significant differences were found between frontal and parietal cortices in experimental group.Conclusion: The immunohistochemical APP reactivity showed different intensities and different morphology in the frontal and parietal cortices in the all experimental group animals were that injected with ketamine in this study. These differences could be related to the requirement of this substance in repair and differentiation of the developing NMDA dependent interneuron impaired by prenatal ketamine exposure.Keywords: Frontal cortex, parietal cortex, amyloid precursor proteins, ketamine, prenatal, immnuohistochemistryCitation: Najm MS, Mubarak HJ, Mohammed LH. Amyloid precursor protein immunohistochemical changes in the newborn mice frontal and parietal cerebral cortices affected by prenatal exposure to ketamine. Iraqi JMS. 2018; 16(2): 191-200. doi: 10.22578/IJMS.16.2.11
Keywords: Frontal cortex; parietal cortex; amyloid precursor proteins; ketamine; prenatal; immnuohistochemistry